Scale of the issue: Mapping the impact of the COVID-19 lockdown on pangolin trade across India. (May 2021) - Aditya, Vikram; Goswami, Rajkamal; Mendis, Aristo; Roopa, Ramya
Abstract: Recent studies have linked COVID-19 induced restrictions to an increase in wildlife crime, with severe yet unknown implications for severely threatened taxa like pangolins. We analyze publicly available online seizure reports involving pangolins across India before (2018–2019) and during the pandemic (March–August 2020), using a longitudinal study design to estimate how lockdowns have impacted pangolin trade. Our analysis indicates a significant increase in seizures reported during the lockdown months of March to August 2020, in comparison to the same period in 2018 and 2019. We discuss the drivers behind this spike in pangolin trade and offer potential conservation measures.